Bio-inspired vs. conventional sandwich beams: A low-velocity repeated impact behavior exploration. (30th April 2018) - Abo Sabah, S.H.; Kueh, A.B.H.; Al-Fasih, M.Y.
Highlights: A study of bioinspired beam (BHSB) repeated impact behavior vs. conventional (HSB). BHSB design has CFRP skins sandwiching a two-layered core (rubber and Al honeycomb). It reduces 50–80% damages and has 2.7–20 times lower bottom skin stresses vs. HSB. This is done by stress spreading action over a wide planar area via the rubber core. Its impact resistance efficiencies are superiorly 1.65–16.22 times higher than HSB. Abstract: A new bio-inspired honeycomb sandwich beam (BHSB) based on the woodpecker's head configuration was developed for repeated low-velocity impact resistance improvement. The new design contains four main layers: carbon fiber reinforced plastic top and bottom skins sandwiching rubber and aluminum honeycomb cores. Impact loadings were performed numerically and experimentally in a repeated manner with a hemispherical steel impactor for three energy levels: 7.28 J, 9.74 J, and 12.63 J. In all cases, stresses developed at the bottom skin of BHSB were significantly smaller with substantially lower damage area while sustaining more number of impact than those of conventional honeycomb sandwich beam (HSB). Also, the impact resistance efficiency indices, I e, which assess overall performance, of both beam designs were compared. I e of BHSB were 1.65–16.22 times higher, conclusively exhibiting its superiority to HSB in repeated impact resisting performance.